John Chrysostom's understanding of the Eucharist in its relation to the Christian life - Amos, Charles Harry (Rhodes University, Faculty of Divinity, Department of Divinity, 1988)
The aim of this thesis is to reveal the intimate relationship between John Chrysostom's Eucharistic theology and the christian life, and that at the Eucharist Man's true being is demonstrated. It investigates Chrysostom's exegetical and oratorical method in order to ascertain how he approached a text and how he delivered his understanding of it. He is a representative of the Antiochene School of Exegesis and his fame as a preacher was a result not so much of his oratorical construction, but of the underlying spiritual unity within the oration. The purpose of all his preaching and exegesis was to evoke a moral response from his hearers. In the consecration of the elements, Chrysostcm displayed a remarkable openness to the varying traditions. He saw reciting the words of institution and invoking the Spirit as effecting consecration. Not only this, but also the moral life of the congregation played its part in effecting consecration. Once the elements had been consecrated, Christ was sacrificed, symbolically and literally, not again but in memory (Greek letters) of the Passion, which thereby becomes a present reality. In Chrysostom's understanding of the real presence he displays yet again an openness to the traditions. Christ is both present symbolically through the elements and literally through the transformation of the elements. The real presence demanded of the communicant a high degree of morality. To approach the Table on which Christ lay demanded a life of virtue, not only from the individual communicant but from the whole community. Those who partook unworthily imitated Judas and shared his fate. The community had to approach the Table in unity. At the Table, however, the community received its unity from Christ, the community became the body of Christ. Through participation and becoming the body of Christ, the community was united with the Godhead . Schism, therefore, was a very serious sin for it tore the body of Christ apart. For Chrysostom, Christ was also present in and intimately united with the poor. The church had to be able to be aware of Christ's presence in the poor and be responsible toward Him. In giving to the poor, the communiicant acknowledged that he/she had received at the Table and also received his/her salvation from Christ through the poor. The whole Eucharistic feast not only fed the christian with spiritual food, but called the communicant away from gross materialism to a life-giving dependance on God. It called the communicant to give to others as he/she had received from Christ.
Keywords: John Chrysostom, Saint, d. 407; Lord's Supper; Lord's Supper -- Biblical teaching